A Cross-linguistic Comparison Between Mongolian and Chinese - Chuluunbaatar B., B; Baltabekova, D. (Journal of Oriental Studies, 2017)
In this article, the authors provide a cross-cultural and cross-linguistic analysis of the Mongolian and Chinese languages. Chinese, as a representative of the isolated languages and Mongolian as agglutinative, typologically very different. However, historical and cultural ties between Mongolia and China left a trace on the lexical fund of both languages. In this article, the authors by means of concrete examples present the similar features and characteristics in Mongolian and Chinese languages.